2020
DOI: 10.1371/journal.pone.0230654
|View full text |Cite
|
Sign up to set email alerts
|

On the track of the ideal turnout: Electromyographic and kinematic analysis of the five classical ballet positions

Abstract: The turnout of the lower extremities is the major component of the classical ballet positions (CPs) and correctly is initiated in the hips. The aim of this research was to determine the differences in the electromyographic and kinematic variables in the five CPs in ballet students with greater and lesser amount of passive hip external rotation (HER). A group of 14 female pre-professional ballet dancers 11-16 years of age participated in the study. Based on the amount of passive HER, participants with higher va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Positions and movements involving end-range extension are an integral part of the dance aesthetic. The biomechanical analysis of the human locomotor system revealed that unfavorable situations are those when muscles are subjected to long isometric tension and when muscles stabilize the multisegment biomechanism bases [ 14 ]. It seems that the flamenco falls well within the scheme of the aforementioned static loads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positions and movements involving end-range extension are an integral part of the dance aesthetic. The biomechanical analysis of the human locomotor system revealed that unfavorable situations are those when muscles are subjected to long isometric tension and when muscles stabilize the multisegment biomechanism bases [ 14 ]. It seems that the flamenco falls well within the scheme of the aforementioned static loads.…”
Section: Discussionmentioning
confidence: 99%
“…This causes a stiffness that could cause overloads in the back muscles. The use of the abdominal muscles and hip extensors (buttocks) is of great importance in the correct pelvis stabilizing process [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The height of the longitudinal arch of the foot seems to be an inborn feature [ 22 ]. Ballet exercises may slightly increase the aforementioned feature, yet they primarily affect foot muscles [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vertical components of ground reaction forces act locally on the ballet dancer’s skeletal system making femoral necks highly mineralised and radial bones (not loaded) osteopenic [ 29 ]. The adoption of ballet positions is responsible for the unnaturally high involvement of lower limb muscles and pathological pelvis positions [ 23 ]. At the same time, feet exercises lead to specific geometric changes in the aforesaid structures, such as hallux valgus [ 27 ].…”
Section: Discussionmentioning
confidence: 99%